IgA Responses Following Recurrent Influenza Virus Vaccination - Abreu, Rodrigo B.; Clutter, Emily F.; Attari, Sara; Sautto, Giuseppe A.; Ross, Ted M. (Frontiers in Immunology, 2020)
Influenza is a highly contagious viral respiratory disease that affects millions of people worldwide each year. Annual vaccination is recommended by the World Health Organization to reduce influenza severity and limit transmission through elicitation of antibodies targeting mainly the hemagglutinin glycoprotein of the influenza virus. Antibodies elicited by current seasonal influenza vaccines are predominantly strain-specific. However, continuous antigenic drift by circulating influenza viruses facilitates escape from pre-existing antibodies requiring frequent reformulation of the seasonal influenza vaccine. Traditionally, immunological responses to influenza vaccination have been largely focused on IgG antibodies, with almost complete disregard of other isotypes. In this report, young adults (18-34 years old) and elderly (65-85 years old) subjects were administered the split inactivated influenza vaccine for 3 consecutive seasons and their serological IgA and IgG responses were profiled. Moreover, correlation analysis showed a positive relationship between vaccine-induced IgA antibody titers and traditional immunological endpoints, exposing vaccine-induced IgA antibodies as an important novel immune correlate during influenza vaccination.